Sinergi Pemerintah Dan Masyarakat Dalam Penanggulangan Persampahan Di Pasar Sentral Kabupaten Enrekang - Sudirman, Fatima; Alyas, Alyas; Abdi, Abdi (Universitas Muhammadiyah Makassar, 2021)
This study aimed to determine the synergy between the government and the community as well as the factors that support and hinder waste management in the central market of Enrekang Regency. Data collection technique used interview, observation and documentation. Data analysis were data reduction, data presentation and conclusions, while the validity of the data using triangulation of sources, techniques and time. The results showed that the synergy of the government and the community in handling waste in the Enrekang central market viewed from 3 dimensions, namely the problem solving aspect through the clean site solid waste service system, aspects of the role of the government in waste management that had not been optimal role of the government both in the form of institutions, operational techniques and regulatory systems and SOPs for the environmental and community services, and aspects of the communication network could be seen that the Government, starting from the Office of the Environment, Districts, and cleaners, had done the right thing to behave and communicate with the community while they were on duty. Keywords: Government and Community Synergy